Ageing, longevity and fitness: towards new paradigms in healthy ageing - Abikusno, Nugroho (Universa Medicina, 2018)
We have nearly reached the end of the second decade of the Millennium. Within 5 years we hope the Third Ageing Summit will be held to discuss lessons learned and future directions in the field of Ageing and Longevity. 1) I mention the word Longevity since many countries especially in the Asia Pacific region, the second Hub of Ageing after the Western world countries, have experienced this phenomenon since the early years of this Millennium.